Implementasi Konsep Hybrid Library Pada Perpustakaan Umum dan Arsip Kota Malang - Stefanie Magdalena; Lintu Tulistyantoro; Hendy Mulyono (Intra, 2019)
The appearence of new generations such as generation Z and Alpha (generation born above in 1997) makes design of some public facilities (especially public libraries) considered old. These generations assume that information sources are more easily obtained through the internet. In addition, a variety of more varied data is one reason this generation prefers online books. From some of the above problems it can be concluded that public facilities, especially libraries, require a change. Therefore, the Hybrid Library concept was chosen as the realm of a more modern digital era library. This concept applies several character designs such as ease of access, speed, and also advanced technologies that are in accordance with the characters of generation Z and Alpha.